Human dendritic cell sequestration onto the Necator americanus larval sheath during ex-sheathing: a possible mechanism for immune privilege - Hassan, A.; Pritchard, D.I.; Ghaemmaghami, A.M. (Cambridge University Press, 2018)
Despite the profound health implications of Necator americanus (N. americanus) infection in humans, many aspects of its interaction with the host immune system are poorly understood. Here we investigated the early events at the interface of N. americanus larvae (L3) and human dendritic cells (DCs). Our data show that co-culturing DCs and the larvae triggers ex-sheathing of hookworms rapidly where a majority of DCs are sequestered onto the larval sheath allowing the ex-sheathed larvae to migrate away unchallenged. Intriguingly, DCs show negligible interaction with the ex-sheathed larvae, alluding to differences between the surface chemistry of the larva and its sheath. Furthermore, blocking of two key C-type lectin receptors on DC surface (i.e. DC-SIGN and mannose receptor) resulted in inhibition of ex-sheathing process and DC sequestration, highlighting the importance of C-type lectins on DCs in the induction of the ex-sheathing. Analyses of DC phenotype and cytokine profile after co-culture with the N. americanus larvae showed an immature phenotype as evidenced by the low expression of the maturation markers and cytokines. These data provide new insights into early events at the interface of human DCs and N. americanus larvae and could explain how L3 evade immune recognition upon initial interaction with DCs.